Literary translation - Wright, Chantal (Routledge, Taylor & Francis Group, 2016)
Routledge Translation Guides cover the key translation text types and genres and equip translators and students of translation with the skills needed to translate them. This is an essential guidebook for all students of literary translation within advanced undergraduate and postgraduate/graduate programmes in translation studies, comparative literature and modern languages.